SEMANTIC GROUPING OF SIGNIFICANT LEXEMAS (Academia Science Repository, 2023)
This article presents ideas about adjectives that express the character-property, property and valuable sign of persons and things. The specific characteristics of the adjectives representing the condition and color sign of persons and things have been revealed.